EFEKTIVITAS MODEL PEMBELAJARAN PjBL BERBASIS STEM UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA - Ika Khoiriyani; Azamul Fadhly Noor Muhammad (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2026)
ABSTRACT The low mathematics learning achievement of students remains a common issue in the learning process at the elementary school level. Various efforts have been made to improve students’ mathematics achievement; however, the implementation of learning models that integrate problem-solving, creativity, and 21st-century skills still requires further investigation, particularly through the application of a STEM-based Project Based Learning (PjBL) model in Islamic elementary schools. Therefore, this study is important to determine the effectiveness of the STEM-based PjBL model in improving students’ mathematics learning achievement. This study aims to examine the effectiveness of the STEM-based Project Based Learning (PjBL) model on the mathematics learning achievement of fourth-grade students at MI Ma’arif Candran. This study employed a quasi-experimental research design. The population consisted of fourth-grade students, with Class IV-A serving as the control group and Class IV-B as the experimental group, each comprising 25 students. Data were collected through tests and interviews using pretest and posttest questions as well as interview sheets. The data were analyzed using the Independent Samples t-Test and N-Gain test. The findings revealed that the STEM-based PjBL model was effective in improving students’ mathematics learning achievement. Students who participated in learning activities using the STEM-based PjBL model demonstrated greater improvement in mathematics achievement compared to those who received conventional instruction. Furthermore, the implementation of this model encouraged active student engagement in the learning process, which positively contributed to their mathematics learning outcomes. ABSTRAK Pembelajaran matematika di sekolah dasar masih menghadapi tantangan berupa capaian belajar peserta didik yang belum optimal. Kondisi ini menunjukkan perlunya pendekatan pembelajaran yang tidak hanya berfokus pada penguasaan konsep, tetapi juga memberi ruang bagi peserta didik untuk berpikir kritis, kreatif, dan terlibat aktif dalam menyelesaikan permasalahan yang berkaitan dengan kehidupan nyata. Dalam konteks tersebut, penerapan Project Based Learning (PjBL) yang dipadukan dengan pendekatan STEM menjadi alternatif yang relevan untuk diterapkan pada jenjang madrasah ibtidaiyah. Kajian ini dilaksanakan pada peserta didik kelas IV MI Ma’arif Candran dengan melibatkan dua kelompok belajar, yaitu kelas IV-A sebagai kelompok kontrol dan kelas IV-B sebagai kelompok eksperimen, yang masing-masing terdiri atas 25 peserta didik. Penelitian ini menggunakan rancangan quasi experiment. Data diperoleh melalui tes awal dan tes akhir yang didukung dengan wawancara, kemudian dianalisis menggunakan uji Independent Sample t-Test serta N-Gain untuk melihat perbedaan dan peningkatan hasil belajar yang terjadi. Temuan penelitian memperlihatkan bahwa peserta didik yang mengikuti pembelajaran matematika melalui PjBL berbasis STEM menunjukkan perkembangan prestasi belajar yang lebih baik dibandingkan peserta didik yang belajar dengan pendekatan konvensional. Selain menghasilkan peningkatan capaian akademik, model pembelajaran ini juga mendorong keterlibatan peserta didik secara lebih aktif selama proses pembelajaran berlangsung. Dengan demikian, PjBL berbasis STEM dapat dipertimbangkan sebagai strategi pembelajaran yang efektif untuk mendukung peningkatan prestasi belajar matematika pada peserta didik sekolah dasar.